Double plating - surgical technique and good clinical results in complex and highly unstable proximal humeral fractures. Issue 8 (August 2021) - Warnhoff, Mara; Jensen, Gunnar; Dey Hazra, Rony-Orijit; Theruvath, Prasobh; Lill, Helmut; Ellwein, Alexander
Highlights: New surgical technique using a precontoured lateral plate and one-third tubular plate at lesser tuberosity for unstable humeral head fractures Double plate osteosynthesis can be used in addition to calcar screws, bone graft augmentation, cement augmentation and additional free screws After mean follow-up of 30.9 months, 72% of patients had excellent or good results regarding the Constant-Murley Shoulder Score Double plating provides high primary stability and has comparable complication rates to single plate osteosynthesis It is an alternative to primary fracture arthroplasty for a younger, active cohort of patients with complex unstable proximal humeral fractures Abstract: Introduction: A stable fixation of highly unstable proximal humerus fractures remains challenging and complication rates, especially secondary varus dislocation, remains high. Different techniques of double plate osteosynthesis have been suggested for the treatment of complex proximal humeral fractures as they are well established for other fractures. The aim of this study was to evaluate an operative technique using an angular stable lateral plate supported by a one-third tubular plate positioned anteriorly at the lesser tuberosity for unstable proximal humeral fractures. Patients and methods: Retrospectively, patients treated with a double plate osteosynthesis were included between January 2014 and December 2017. Out of 31, 25 patients (80.6%) with an average age of 53.1 years ± 12.5 were available for follow-up. 60% of the patients were male. The clinical evaluation consisted of a physical examination and standardised questionnaire including subjective and objective shoulder scores like the Constant-Murley Shoulder Score, Simple Shoulder Score, and Subjective Shoulder Value. Results: After a mean follow-up of 30.9 months (range, 12-76 months) eighteen patients (72%) had either excellent or good results regarding the Constant-Murley Shoulder Score with a mean value of 77 points ± 17. Average Simple Shoulder Score was 76% ± 0.2 and Subjective Shoulder Value 72% ± 0.2%. Mean NSA at time of follow-up 135° ± 13°. Nine patients had an implant-removal, five in combination with arthrolysis after a mean of 7.2 months. Three patients underwent surgery for secondary arthroplasty. The study shows a complication rate of 16%. No revision-surgery because of secondary varus dislocation was reported. Discussion: Arthroplasty is the less favourable treatment for a younger, active cohort of patients with highly unstable proximal humeral fractures as results are not as good and options for revision are limited. Double plate osteosynthesis can be used in addition to calcar screws, bone graft augmentation, cement augmentation and additional free screws for more multidirectional stability and shows good clinical results despite a higher rate of avascular necrosis and high primary stability with comparable complication-rates to single plate osteosynthesis. It seems to be a valid alternative to primary fracture arthroplasty and can prevent secondary varus displacement.